Pelatihan Media Presentasi Powtoon dan Sparcol Untuk Guru SD Negeri 9 Purwodadi, Grobogan - Achmad Fathoni; Ajib Rosyadi; Indra Gunawan; Muhammad Taufik Hidayat; Afrin Puspasari (Prosiding University Research Colloquium, 2019)
The purpose of this social service is to provide learning mediatraining based on the presentation application, Sparcol and Powtoon.This activity was given to teachers in Elementary School 9Purwodadi. The social service session consists of installing anapplication, creating an account, adding images and text, changingthe background, and saving the results that have been made. Themodel used is a workshop model with lectures, demonstrations,question and answer and direct practice methods. Evaluation is doneby distributing information and motivation questionnaires toparticipants and product checklists. In general, participants claimedthat the training schedule was right, the time sharing (lectures,demonstrations, question-answer and direct practice) was also feltpositively by the participants. Participants are satisfied with the topicpresented and feel that most of the expectations and objectives of thesocial service are fulfilled. Evaluation results indicate that thematerial delivered can be followed well.